Lockdown Measures Against the Spread of the COVID-19 Pandemic: Negative Effects for People Living With Depression - Czaplicki, Andreas; Reich, Hanna; Hegerl, Ulrich (Frontiers in Psychology, 2022)
The Covid-19 pandemic and the measures to restrict the spread of the virus were associated with limitations in health care and changes in depression-related lifestyle (loss of daily structure, lack of exercise, and extended bed and sleep times) for depressed patients that are known to negatively affect the course of depression. This paper examines, i) the reporting of worsening illness status as a result of COVID-19-related measures among individuals with depressive disorders and ii) whether this worsening was related to restrictions in health care for depression or changes in depression-related lifestyle. The analysis was based on a population-representative survey of the German population aged 18-69 years (N=5,135 respondents, comprising a subgroup of N=1,038 persons suffering from depression and N=598 persons who spent the lockdown primarily in home isolation). The key findings were: 49% (N=505) of respondents with self-reported diagnosed depression reported that the measures against the pandemic had a negative impact on their depressive illness (new depressive episode, worsening of symptoms, suicidal impulses, suicide attempt and other negative consequences). Of those who reported impaired health care for their depressive illness, 70% (N=276) also reported a worsening of their depressive illness. This was a significantly higher percentage than for those who did not experience impairment of health care (36%, N=229, p<0.001). Of those who reported changes in depression-related lifestyle (loss of daily structure, lack of exercise or extended bed and sleep times), 58% (N=308) reported a worsening of their depressive illness. This was a significantly higher percentage than for those who did not exhibit any of the outlined behaviours (28%, N=19, p<0.001). Worsening of the depressive illness was most common among those who reported lack of daily structure or extended bedtimes (67%; N=230 resp. N=226). People who mentioned lack of exercise also reported a worsening of their depressive illness (59%; N=271). These findings underscore the need to consider the suffering and possible increased suicide risk induced by the measures against die COVID-19 when looking for an optimal risk-benefit ratio of measures taken. Our study highlighted the importance of maintaining health care even in crisis situations and to ensure guideline-based treatment.